Fabrication of highly efficient ultraviolet absorbing PVDF membranes via surface polydopamine deposition. Issue 4 (18th September 2017) - Dong, Li; Liu, Xiangdong; Xiong, Zhengrong; Sheng, Dekun; Lin, Changhong; Zhou, Yan; Yang, Yuming
ABSTRACT: Polydopamine (PDA) layers and particles self‐polymerized by dopamine have ultraviolet (UV) absorbing property besides versatility and adhesive ability. Herein, a facile strategy for preparing poly(vinylidene fluoride) (PVDF) membrane coated with a thick PDA layer was developed to decrease UV transmittance through the surface modification of PVDF membrane. The PVDF membrane was modified by PDA deposition after pretreated with KOH/alcohol and KMnO4 /KOH solution. Furthermore, we investigated the effect of coating conditions such as concentration of dopamine and Tris–HCl buffer solution, coating time, and temperature on the performance of membranes. The characterization results indicated that it is more conductive for PDA deposition on the surface PVDF‐OH films than original PVDF films. Most importantly, UV transmittance of PVDF‐OH film modified in dopamine solution under optimum condition for one time can decrease to as low as 0.122% at 320 nm, which showed excellent UV‐shielding property. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45746. Abstract :